Simulation-Based Training – Evaluation of the Course Concept “Laparoscopic Surgery Curriculum” by the Participants - Köckerling, Ferdinand; Pass, Michael; Brunner, Petra; Hafermalz, Matthias; Grund, Stefan; Sauer, Joerg; Lange, Volker; Schröder, Wolfgang (Frontiers in Surgery, 2016)
Introduction The learning curve in minimally invasive surgery is much longer than in open surgery. This is thought to be due to the higher demands made on the surgeon’s skills. Therefore, the question raised at the outset of training in laparoscopic surgery is how such skills can be acquired by undergoing training outside the bounds of clinical activities to try to shorten the learning curve. Simulation-based training courses are one such model. Methods In 2011, the surgery societies of Germany adopted the “laparoscopic surgery curriculum” as a recommendation for the learning content of systematic training courses for laparoscopic surgery. The curricular structure provides for four 2-day training courses. These courses offer an interrelated content, with each course focusing additionally on specific topics of laparoscopic surgery based on live operations, lectures, and exercises carried out on bio simulators. Results Between 1st January, 2012 and 31st March, 2016, a total of 36 training courses were conducted at the Vivantes Endoscopic Training Center in accordance with the “laparoscopic surgery curriculum.” The training courses were attended by a total of 741 young surgeons and were evaluated as good to very good during continuous evaluation by the participants. Conclusion Training courses based on the “laparoscopic surgery curriculum” for acquiring skills in laparoscopy are taken up and positively evaluated by young surgeons.